Evolutionary Comparison of the Developmental/Physiological Phenotype and the Molecular Behavior of SPIRRIG Between Arabidopsis thaliana and Arabis alpina - Stephan, Lisa; Jakoby, Marc; Hülskamp, Martin (Frontiers in Plant Science, 2021)
Beige and Chediak Higashi (BEACH) domain proteins mediate membrane-dependent processes in eukaryotic cells. The plant BEACH domain protein SPIRRIG in A. thaliana (AtSPI) was shown to display a similar molecular behavior as its yeast and animal homologs, along with a range of cell morphological defects. In addition, AtSPI was shown to interact with the P-body component DCP1, to differentially effect RNA levels and to be involved in the regulation of RNA stability in the context of salt stress responses. To determine, whether the dual function of SPI in apparently unrelated molecular pathways and traits is evolutionary conserved, we analyzed three Aaspi alleles in Arabis alpina. We show that the molecular behavior of the SPI protein and the role in cell morphogenesis and salt stress response are similar in the two species, though we observed distinct deviations in the phenotypic spectrum.